Assessment of the Capacity of TVET and University Hospitality Schools in offering Food Safety and Hygiene Training in Kenya - Wandolo, Monica A.; Ndiritu, Prof. Douglas; Khayiya, Dr. Rosemarie; Mugendi, Dr. Beatrice W. (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the capacity of TIVET and University hospital schools in offering food safety and hygiene training in Kenya. The major areas of focus were the general availability of basic equipment, whether the available equipment were modern, extent of use of available equipment and workshop organization including drainage. A total of 671 respondents participated in the study (Comprising 249 from universities, 250 from Institutes of Technology, 64 from Polytechnics and 128 from Technical Institutions). Primary data sources included using structured questionnaires, taking photographs, oral interviews, observation check list and focus group discussions. Secondary sources, on the other hand, involved retrieving information from desk research where journals, books and other relevant literature were obtained. Both descriptive and inferential statistics were used to analyze the quantitative data while content analysis was used to analyze the qualitative data. The analyzed data were presented in terms of graphs and tables. The findings revealed that in the two categories of institutions, equipment/tools in universities were relatively higher in number compared to the other categories. In addition, not all the available tools were modern. It was observed that only 78% of the available tools were modern while 19% were not. This finding revealed that there was underutilization of available facilities in the institutions. A summary of various aspects of capacity of institutions in providing training on food safety and hygienic practices and adopting proper hygienic practices revealed that universities had a high capacity (63.5 %) relative to the other categories. On the other hand, the lowest capacity level was observed in institutes of science and technology, which had 46.4%. The findings further revealed that some institutions were well-prepared in terms of equipment and facilities, while the majority were not. Observation revealed that most of the workshops used, particularly in TVET institutions, were originally used for other purposes such as classrooms, home economics laboratory or were stores converted to production workshops. As a result, such institutions lacked basic equipment. The study concluded that TIVET and Universities had inadequate facilities and resources required to offer food safety and hygiene training courses. It was recommended that ministry of education should to identify a monitoring team to visit hospitality training workshops to assess the capacity in terms of infrastructure, facilities and equipment to determine the level of requirement in every institution. This would pave way for the upgrading of the facilities to a level that they would offer adequate training to the enrolled students.